What determines euro area bank CDS spreads? - Jan Annaert; Marc De Ceuster; Patrick Van Roy; Cristina Vespro (National Bank of Belgium, 2010)
This paper decomposes the explained part of the CDS spread changes of 31 listed euro area banks according to various risk drivers. The choice of the credit risk drivers is inspired by the Merton (1974) model. Individual CDS liquidity and other market and business variables are identified to complement the Merton model and are shown to play an important role in explaining credit spread changes. Our decomposition reveals, however, highly changing dynamics in the credit, liquidity, and business cycle and market wide components. This result is important since supervisors and monetary policy makers extract different signals from liquidity based CDS spread changes than from business cycle or credit risk based changes. For the recent financial crisis, we confirm that the steeply rising CDS spreads are due to increased credit risk. However, individual CDS liquidity and market wide liquidity premia played a dominant role. In the period before the start of the crisis, our model and its decomposition suggest that credit risk was not correctly priced, a finding which was correctly observed by e.g. the International Monetary Fund
Keywords: G01; G12; G21; 330; credit default spreads; credit risk; financial crisis; financial sector; liquidity premia; structural model; Kreditderivat; Kreditversicherung; Kreditrisiko; Liquidität; Finanzkrise; Eurozone; EU-Staaten